A Home in Drayton Valley : A Novel - Sawyer, Kim Vogel (Minneapolis, Minn. : Bethany House, 2012)
Escaping the poor conditions of 1880 New York, Tarsie Raines sets off for Kansas aboard an unusual wagon train, but when tragedy strikes, Tarsie is thrown into a partnership with Joss Brubacher that leaves them both questioning God and their future.
Keywords: Frontier and pioneer life -- Fiction -- Kansas; Man-woman relationship -- Fiction; Historical fiction; Christian fiction